Overcoming the Impact of COVID-19 in the Densely Populated Area through “Taman Momong” - Istiadah Istiadah; Aprilia Mega Rosdiana; Muallifah Muallifah (Sawwa: Jurnal Studi Gender, 2021)
The COVID-19 pandemic in Indonesia influenced the public health sector and disrupted childcare work, especially for those in dense settlements and classified as low-income households. This research aims at helping densely populated communities to provide care facilities by optimizing free children’s playgrounds and learning spaces to support children’s physical and psychological growth and development during the pandemic. By employing the Participatory Action Research (PAR) method, this study generated two main results, first, “Taman Momong”, the child-friendly park, equipped with children’s playground facilities. Second, the park also has a mini library for children with various educational activities needed by the community such as parenting workshops that integrate children’s rights perspective, training on the use of Moringa and Aloe Vera plants to improve family nutrition, including children's nutrition, and training on herbal medicines to maintain family health. Thus, “Taman Momong” as a green space is beneficial in improving the physical and mental health of the community. Moreover, community activities at “Taman Momong” indicates that the park plays an important role in overcoming parenting problems during the COVID-19 pandemic. This research also found that collaboration between society with the government is essential in building public facilities such as child-friendly parks to support childcare work. This study recommends other communities adopt “Taman Momong” model to enhance their health status and childcare quality.